Changes of optical coherent tomography parameters after phacoemulsification in acute angle-closure glaucoma - N. A. Bakunina; L. N. Kolesnikova (Российский офтальмологический журнал, 2018)
Purpose: to analyze the main pathogenic factors of closing and opening of the anterior chamber angle in patients with acute angle-closure glaucoma before and after hacoemulsification using optical coherence tomography (OCT) data. Material and methods. The study involved 35 patients aged 50-81 (ave. 65 years) with acute angle-closure glaucoma. The control group included 15 healthy individuals (30 eyes) with initial or immature cataract and no disturbed eye pressure and 12 patients with primary open-angle glaucoma aged 55 to 80. All patients underwent phacoemulsification. Results. Increased choroidal thickness, as well as a more pronounced difference between the thickness of the cornea in the center and the periphery, was revealed in angle-closure glaucoma as compared to the control groups. Phacoemulsification of the lens in eyes with acute angle-closure glaucoma reduces the choroidal thickness, decreases IOP, improves visual functions, extends anterior chamber angle, and increases the volume and depth of the anterior chamber of the eye. Conclusion. OCT data may be useful in the evaluation of treatment results, diagnosis and prognosis of acute primary angle closure glaucoma // Russian ophthalmological journal. 2017; 10 (2): 10-6. (in Russian). doi: 10.21516/2072-0076-2017-10-2-10-16.